Analysis of The Influence of Website Quality, Sales Promotions, and Prices on Purchase Decisions Through Consumer Trust on Jagoujian.com - Meykel Djuuna; Nur Sayidah; Sri Utami Ady (PT Mattawang Mediatama Solution, 2024)
The rapid development of internet technology provides many conveniences in communicating and is able to change people's behavior, including purchasing decisions which are reflected in the level of product/service sales. This becomes a business opportunity to provide an online or Edutech-based forum or platform, one of which is jagoujian.com. However, the company's target of selling tryout services on jagoujian.com has not yet been achieved. Therefore, this research is conducted to analyze the factors contributing to the failure of meeting the target of the website. The purpose of this study is to analyze the influence of website quality, sales promotion, and pricing on purchasing decisions through consumer trust on jagoujian.com. The study sample involves 304 members of jagoujian.com with 75 respondents. Partial least squares structural equation modeling (PLS-SEM) is the chosen method to analyze the sample in this study. The results indicate that the quality of the website and pricing significantly influence the purchasing decisions of jagoujian.com users. However, sales promotions do not exhibit a significant influence on the purchasing decisions of jagoujian.com users. Website quality has a significant influence on the purchasing decisions of jagoujian.com users. Pricimg has also shown a positive and significant influence on the purchasing decisions of jagoujian.com users, sales promotions have an influence on the purchasing decisions of jagoujian.com users, consumer trust has a significant influence on the purchasing decisions of jagoujian.com users, website quality has shown a significant influence on purchasing decisions through consumer trust, pricing has a significant effect on purchasing decisions through consumer trust, sales promotions have an influence but not significantly on purchasing decisions through consumer trust.